2018
DOI: 10.33687/pbg.006.01.2171
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of F4 Bread Wheat (Triticum aestivum l.) Genotypes for Genetic Variability, Heritability, Genetic Advance and Correlation Studies

Abstract: This research was carried out to check genetic variability, heritability and genetic advance in 11 F4 bread wheat (Triticum aestivum L.) genotypes (10 F4 lines and one check) in a randomized block design with three replications at the University of Agriculture Peshawar, Pakistan during 2015-16. Data was/were taken on parameters such as days to heading (days), plant height (cm), flag leaf area (cm2), spike length (cm), grain weight spike-1 (g), 1000-grain weight (g), grain yield plant-1 (g), biological yield pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In these population, its character was controlled genetically, so perhaps it will be inherited to next generations. Sohail et al (2018) said that characters whose high heritability values could be selected by single plant selection for the next generation.…”
Section: Broad-sense Heritabilitymentioning
confidence: 99%
“…In these population, its character was controlled genetically, so perhaps it will be inherited to next generations. Sohail et al (2018) said that characters whose high heritability values could be selected by single plant selection for the next generation.…”
Section: Broad-sense Heritabilitymentioning
confidence: 99%
“…The study of heritability, genetic advance, and genotypic and phenotypic coefficient of variation helps find the magnitude and nature of variation in germplasm. Thus, crop improvement depends on genetic variability in breeding material (Sohail et al, 2018;Ahmed et al, 2019a;Arifuzzaman et al, 2020). Selection of the superior phenotype type is possible only when the genotype (G) and phenotype (Ph) are strongly correlated.…”
Section: Introductionmentioning
confidence: 99%
“…. Recently in Pakistan, various researchers (Baloch et al, 2014;Sohail et al, 2018;Rattar, 2019;Khan, 2020) found that traits like spike length, grains spike -1 , seed index, biological yield and harvest index disclosed positive and significant associations with grain yield. However, these all above studies were carried out in non-saline soil conditions.…”
Section: Introductionmentioning
confidence: 99%